2016
DOI: 10.1007/s11051-016-3447-5
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent cytotoxicity of yttrium oxide nanoparticles on primary osteoblasts in vitro

Abstract: Yttrium oxide nanoparticles are an excellent host material for the rare earth metals and have high luminescence efficiency providing a potential application in photodynamic therapy and biological imaging. In this study, the effects of yttrium oxide nanoparticles with four different sizes were investigated using primary osteoblasts in vitro. The results demonstrated that the cytotoxicity generated by yttrium oxide nanoparticles depended on the particle size, and smaller particles possessed higher toxicological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Treatment with Y 2 O 3 NPs showed that cell growth was significantly decreased and ROS levels were increased in marine phytoplanktons (Castro‐Bugallo, González‐Fernández, Guisande, & Barreiro, ). Y 2 O 3 NPs produced cytotoxicity in a size‐ and dose‐dependent manner in osteoblasts due to ROS generation (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with Y 2 O 3 NPs showed that cell growth was significantly decreased and ROS levels were increased in marine phytoplanktons (Castro‐Bugallo, González‐Fernández, Guisande, & Barreiro, ). Y 2 O 3 NPs produced cytotoxicity in a size‐ and dose‐dependent manner in osteoblasts due to ROS generation (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…3YTZP is a chemically stable dental ceramics [ 26 ]; however, the consequences of various environments in a human body, the dissolution of yttria, have considered before applying as a biomedical material. It has already been reported that yttria is a cytotoxic element depending on the magnitude of exposure and is the size and concentration-dependent [ 14 16 ]. Therefore, the biocompatibility of those fully stabilized zirconia with higher yttria content still needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers reported that the Y 2 O 3 nanoparticles (NPs) exhibit potential cytotoxicity to human foreskin fibroblasts cells and human embryonic kidney (HEK293) cells [ 14 15 ]. It was also demonstrated that in osteoblast, the cytotoxicity produced by Y 2 O 3 NPs was in a dose and size-dependent manner [ 16 ]. In the case of dental crown or restoration, the most critical problems are local toxicity, by substance release from dental materials, which causes inflammation or necrosis in adjacent tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are currently available regarding the effect of TCE on the environment or on organisms, despite its increasing abundance. To date, the scarce data concerning yttrium toxicity ( Hirano et al, 1993 ; Li et al, 2015 ; Zhang et al, 2016 ; Trifuoggi et al, 2017 ; Wang Y. M. et al, 2017 ) mostly focus either on yttrium nanoparticles ( Zhang et al, 2016 ; Zhou et al, 2016 ) or indirect effects caused by the use of the radioactive isotope yttrium-90 ( Riaz et al, 2014 ). Although yttrium toxicity has been observed for some organisms, the associated detrimental mechanisms remain unknown ( Hirano et al, 1993 ; Li et al, 2015 ; Zhang et al, 2016 ; Trifuoggi et al, 2017 ; Wang Y. M. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%